Outcome of acute renal failure associated with cardiac surgery in infants - Romão Jr,João Egídio (2000)
OBJECTIVE: To analyze the impact of acute renal failure (ARF) on the evolution of infants undergoing cardiac surgery. METHODS: We assessed 15 infants undergoing cardiac surgery who developed (ARF). Their demographic, clinical and surgical data, and evolution were analyzed. RESULTS: Their mean age was 4.4±4.0 months (8 days to 24 months). Twelve infants were males, and 4 patients already had ARF at surgery. The primary cause of ARF was immediate acute cardiac dysfunction in 10 infants, cardiac dysfunction associated with sepsis in 2 infants, and isolated sepsis in 3 infants. All children depended on mechanical ventilation during their postoperative period, 14 infants used vasoactive drugs, and 11 had an infectious process associated with ARF. Thirteen infants required dialytic treatment. Eleven infants developed oluguric ARF, and all had to undergo peritoneal dialysis; of the 4 patients with non-oliguric, 2 required dialysis, the main indication being hypervolemia. Of these 13 dialyzed infants, 4 died in the first 24 hours because of the severity of the underlying cardiac disease (mean urea level of 49±20 mg/dl). The mortality rate for the entire group was 60% , and it was higher among the patients with oliguria ARF (73% vs 25%, p<0.001). The cause of death was acute cardiac dysfunction in 6 infants (early type-1ARF) and sepsis in the 3 remaining infants (late type-2 ARF). CONCLUSION: The mortality rate of ARF associated with cardiac surgery in infants was hight, being higher among children with oliguria; peritoneal dialysis was indicated due to clinically uncontrolled hypervolemia and not to the uremic hypercatabolic state.